3D Ti3C2Tx MXene/C hybrid foam/epoxy nanocomposites with superior electromagnetic interference shielding performances and robust mechanical properties. (August 2019) - Wang, Lei; Qiu, Hua; Song, Ping; Zhang, Yali; Lu, Yuanjin; Liang, Chaobo; Kong, Jie; Chen, Lixin; Gu, Junwei
Abstract: Few-layered Ti3 C2 Tx MXene was prepared by ionic intercalation and sonication-assisted method. Porous three-dimensional (3D) Ti3 C2 Tx MXene/C hybrid foam (MCF) was fabricated by sol-gel followed by thermal reduction. The MCF/epoxy EMI shielding nanocomposites were obtained via vacuum-assisted impregnation followed by curing process. When the mass fraction of MCF was 4.25 wt% (MCF-5), the MCF-5/epoxy EMI shielding nanocomposites exhibited the optimal electrical conductivity of 184 S/m and the maximum EMI SE of 46 dB, 3.1 × 10 4 and 4.8 times higher than that of MCF-0/epoxy nanocomposites (without Ti3 C2 Tx MXene), respectively. Furthermore, the corresponding Young's modulus of 3.96 GPa and hardness of 0.31 GPa was increased by 13% and 11%, respectively. Conductive networks can realize the attenuation and dissipation of electromagnetic waves by multiple reflection & reabsorption, and absorption is main shielding mechanism. Unique 3D conductive networks of MCF would expand wider application of the Ti3 C2 Tx MXene/polymer-based nanocomposites in high-tech EMI shielding fields.